Establishment of jujube anther culture and plant regeneration system - GUO Kaiwen; XU Chongchong; HU Yaning; HUANG Jian (Guoshu xuebao)
[Objective] Ziziphus jujuba is an economically important tree species in China. The establishment of its anther culture regeneration system is of great significance for accelerating genetic improvement and polyploid breeding. However, the existing anther culture system faces challenges such as low callus induction rates and difficulties in adventitious bud differentiation. In this study, three jujube varieties, Dongzao, Junzao and Qiyuexian, were used as materials. By optimizing the ratios of plant growth regulators, carbon sources, and cultivation conditions, an efficient anther culture regeneration system was established. [Methods] Young floral buds of Dongzao, Junzao and Qiyuexian at the green to yellowish-green stage (pollen at the late uninucleate stage) were used as the experimental materials. Flower buds were rinsed with running tap water for 0.5-1 h, transferred to a laminar flow hood, surface-sterilized with 75% ethanol for 30-60 s, followed by immersion in 0.1% (w/V) HgCl2 solution for 10 min, and rinsed 4-6 times with sterile water. Anthers were aseptically excised from flower buds in a culture dish. The anthers were inoculated onto callus induction media with 9 combinations and concentrations of plant growth regulators (PGRs), with varying durations of pretreatment at 4 ℃ (0, 1, 3, 5, 7 d) and carbon sources (Maltose, Sucrose and Glucose). Callus induction rates were recorded after 30 d of culture. Induced callus clusters were transferred to MS medium supplemented with distinct PGR types and concentrations for proliferation under dark conditions for 20 d, and then callus proliferation coefficients were calculated. For differentiation, two basal medium (MS and WPM) were used, supplemented with 20 g·L-1 maltose and varying PGR combinations (18 treatments in total). Well-growing callus lines of each genotype were inoculated and cultured under light for 50 d to assess adventitious bud differentiation rates. Ploidy of regenerated plantlets was determined via flow cytometry using diploid Ziziphus jujuba var. spinosa tissue-cultured seedlings as controls. For rooting, 2 cm stem segments of Dongzao with vigorous growth from subcultures were transferred to rooting media, and rooting rates were evaluated after 30 d. [Results] The optimal callus induction medium for anthers of Dongzao, Junzao and Qiyuexian was MS + 30 g·L-1 maltose + 1.0 mg·L-1 2,4-D + 0.4 mg·L-1 TDZ + 0.4 mg·L-1 NAA, achieving an induction rate of 59.33%, 64.00%, and 58.67%, respectively. The induction rate was higher than those achieved by the individual application of 2, 4-D alone or the sole combination of TDZ and NAA. The effects of different hormones and genotypes on callus induction rates were both significant. The influence of the three hormones on callus induction rates was in the order of 2, 4-D> NAA>TDZ. Calli induced by the addition of maltose were mostly yellowish-white in color and grew fast, with the highest induction rate of callus tissue at a concentration of 30 g·L-1. Pretreatment at 4 ℃ increased the callus induction rates in Dongzao and Qiyuexian, but had no significant effect in Junzao. Among them, the induction rate of Dongzao anthers was higher at 1 to 3 d of low-temperature treatment, with an induction rate of 60.67% in 1 d chilling pretreatment, and significantly decreased to 36.67% under 5 d chilling pretreatment. The induction rate of Junzao anthers showed no significant difference under different low-temperature treatment times, remaining around 47%, indicating that low-temperature treatment had a limited effect on its induction rate. The induction rate of Qiyuexian anthers was highest (38.67%) under 3 d of low-temperature treatment. The culture media suitable for the callus proliferation of the anthers of Dongzao, Junzao and Qiyuexian were 2.5 mg·L-1 TDZ + 0.4 mg·L-1 IBA + 0.1 mg·L-1 NAA, 1.0 mg·L-1 TDZ + 0.8 mg·L-1 IBA, 1.5 mg·L-1 TDZ + 0.8 mg·L-1 IBA, respectively, and the proliferation coefficients were 88.89%, 81.11% and 78.89% respectively. WPM basal medium was superior for differentiation, with hormone combinations yielding differentiation rates of 48.00%, 29.33%, and 33.33% for Dongzao (0.8 mg·L-1 TDZ + 0.5 mg·L-1 IBA + 0.2 mg·L-1 NAA), Junzao (1.0 mg·L-1 6-BA + 0.5 mg·L-1 TDZ + 0.5 mg·L-1 NAA), and Qiyuexian (1.0 mg·L-1 TDZ + 0.5 mg·L-1 IBA + 0.2 mg·L-1 NAA), respectively. Dongzao exhibited the highest callus induction and differentiation rates, with anther-derived callus demonstrating superior morphological quality. Compared to Junzao and Qiyuexian, Dongzao showed significantly higher efficiency in callus and adventitious bud induction, accompanied by vigorous growth of regenerated plantlets. These findings collectively indicate that genotype is a critical determinant in the in vitro induction of adventitious buds from anther-derived callus. Among the 36 regenerated plants of Dongzao, 33 (92%) were diploid (2n) and 3 (8%) were haploid-diploid chimeras. All the 5 regenerated plants of Junzao were diploid (2n). Among the 8 regenerated plants of Qiyuexian, 6 (75%) were diploid (2n) and 2 (25%) were haploid (n). For rooting, 1/2 MS medium supplemented with 0.4 mg·L-1 IBA and 0.3 g·L-1 activated charcoal achieved an 87.5% rooting rate for Dongzao. [Conclusion] This study established an in vitro anther culture system for Dongzao, Junzao and Qiyuexian, and obtained regenerated plants. The optimal induction, proliferation, and differentiation media for anthers of Dongzao, Junzao and Qiyuexian were determined, revealing the impact of genotype. Haploid regenerated plants of Qiyuexian were obtained, providing new materials for the breeding of jujube varieties.